The Road to an Agreement on Missions The Quarrel between Portugal and the Holy See Regarding the Missionary Policy for the Portuguese Empire in Africa (c.1880–1910) - Dores, Hugo Gonçalves 1983- (2021)
Throughout the nineteenth century, Portugal demanded recognition of the so-called ‘historical rights of the Royal Patronage’ by the Holy See as part of its missionary policy for Africa. These claims promptly led to a prolonged conflict over the action of the Propaganda Fide and Portuguese missionary achievements. While Lisbon feared the denationalization of missionary work, Rome was concerned about Portugal’s internal policies on religious matters and its perceived inabilities to deal with the missionary challenges of the time, especially the Protestant competition over African hearts and minds. This text follows the discussions between Portugal and the Holy See over the missionary question, examining their confrontational and, apparently, irreconcilable positions, and the attempts made to regulate the exercise of the Royal Patronage through a concordat that became impossible to reach until the conclusion of a fragile and arguable modus vivendi concluded just before the implantation of the Republican regime in 1910.
Keywords: Concordat; Africa; Empire; Mission; Holy See; Portugal